A Case Report of Aphasia Patient with Repetition Restoration - Shuqing LI; Hong WANG; Zhuoming CHEN; Yanhong DAI (康复学报)
Objective:To explore the correlation between the restoration of repetition and the functional connectivity alternation in the brain of aphasia patients.Methods:An aphasia patient treated with speech rehabilitation approach was evaluated with aphasia battery of Chinese (ABC) and required the resting-state fMRI before and after the treatment. The Broca area, angular gyrus and Wernicke area in the left hemisphere were choosed as the region of interest (ROI), the change of language function was observed, and the correlation coefficient of functional connectivity between three ROIs were calculated.Results:After speech therapy, the word repetition score was obviously increased, but the sentence repetition score was not significantly improved. The correlation coefficient of functional connectivity between Broca area and Wernicke area was obviously increased after speech therapy. The correlation between Wernicke area and angular gyrus switched from negative correlation to positive correlation.Conclusion:The restoration of word repetition may related to the strengthen of functional connectivity of Broca-Wernicke pathway and angular-Wernicke pathway in the left hemisphere.